Influence of ex vivo purging with CliniMACS CD34+ selection on outcome after autologous stem cell transplantation in non‐Hodgkin lymphoma. (25th November 2013) - Yahng, Seung‐Ah; Yoon, Jae‐Ho; Shin, Seung‐Hwan; Lee, Sung‐Eun; Cho, Byung‐Sik; Eom, Ki‐Seong; Kim, Yoo‐Jin; Lee, Seok; Kim, Hee‐Je; Min, Chang‐Ki; Kim, Dong‐Wook; Lee, Jong‐Wook; et al.
Summary The major limitation of autologous stem cell transplantation (auto‐SCT) in non‐Hodgkin lymphoma (NHL) is relapse. Although autologous graft contamination may be a potential cause, prior purging of the autograft remains controversial. Therefore, we retrospectively analysed 56 consecutive patients with NHL receiving auto‐SCT at complete (n = 41) or partial remission (n = 15). Among them, 24 patients underwent autograft manipulation with positive selection of CD34+ cells using a CliniMACS device (purged group). Twenty‐five patients had received ≥2 previous chemotherapy regimens before auto‐SCT. After a median follow‐up of 41·4 months, transplant‐related mortality was observed only in unpurged group (n = 2; 3·6%). The 3‐year overall survival (91·7% vs. 56·1%, P = 0·009) and progression‐free survival (78·7% vs. 53·1%, P = 0·034) favoured CD34+ purification. While neutrophil recovery was similar, platelet recovery was delayed in the purged group. Cytomegalovirus reactivation was predominantly observed in the purged group, although no other clinically unmanageable infectious complications occurred. Although this study has the inevitable limitations of heterogeneity in previous treatment and NHL subtypes, and a small number of patients analysed, the high survival rate in the purged group may suggest the need for prospective randomized trials to determine the role of CD34+ purification in auto‐SCT for NHL.